Renal cortical transit time as a predictor for pyeloplasty in pediatric patients with unilateral hydronephrosis - Stuart More; John Lazarus; Anita Brink (World Journal of Nuclear Medicine)
Majority of patients with unilateral hydronephrosis (HN) detected on ultrasound do not require pyeloplasty. The measurement of the cortical transit time (CTT) has been demonstrated by several authors to predict the need for patients who may require pyeloplasty. The study aimed to assess if CTT would have predicted a drop in differential renal function (DRF) in patients with unilateral HN on the affected side and to assess whether CTT would differ on the first renogram between those patients who had a pyeloplasty and those who did not have a pyeloplasty. Sixty-eight patients with at least two renograms with unilateral HN with a normal contralateral kidney were observed retrospectively. The CTT was recorded for each kidney. Renograms were processed three times to measure the DRF. The mean of the three DRF measurements was used for analysis. The mean CTT of the left and right hydronephrotic kidneys was 6.0 min and 6.7 min, respectively. The relationship between CTT and DRF as well as CTT and anterior posterior diameter in the first renogram of those patients who did not have a pyeloplasty was statistically significant (P < 0.05). In the 20 patients who had a pyeloplasty, there was a drop of more than 10% in the DRF of three patients. No significant difference was found in CTT or DRF when comparing the group who had surgery against the group who did not have surgery. The current study was unable to demonstrate in our series of patients that CTT can predict a drop in DRF in those patients who would require pyeloplasty.